2022
DOI: 10.1177/03635465221085030
|View full text |Cite
|
Sign up to set email alerts
|

Revision Hip Arthroscopy With Labral Reconstruction for Irreparable Labral Tears in Athletes: Minimum 2-Year Outcomes With a Benchmark Control Group

Abstract: Background: The incidence of revision hip arthroscopy with labral reconstruction in athletes is increasing. However, the outcomes of revision hip arthroscopy with labral reconstruction in athletes have not been well established. Purposes: (1) To report minimum 2–year patient–reported outcome (PRO) scores and return to sports (RTS) characteristics for high–level athletes undergoing revision hip arthroscopy with labral reconstruction and (2) to compare clinical results with those of a propensity–matched control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…When the labrum is too damaged to be repaired or augmented, labral reconstruction seems to be the only surgical option to restore the morphology and function of the torn labrum. 11,15,22,23,31 However, our previous results have shown that poor tissue healing occurred because of the slow and insufficient vascular ingrowth within the articular half of the reconstructed autograft. 25 Given that, this study aimed to explore the possibility of improving the vascularization of the inner half through bone marrow stimulation and to find out whether the volume of the regrown tissue is sufficient to fill the labral defect after microfracture at the bony rim of the acetabulum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the labrum is too damaged to be repaired or augmented, labral reconstruction seems to be the only surgical option to restore the morphology and function of the torn labrum. 11,15,22,23,31 However, our previous results have shown that poor tissue healing occurred because of the slow and insufficient vascular ingrowth within the articular half of the reconstructed autograft. 25 Given that, this study aimed to explore the possibility of improving the vascularization of the inner half through bone marrow stimulation and to find out whether the volume of the regrown tissue is sufficient to fill the labral defect after microfracture at the bony rim of the acetabulum.…”
Section: Discussionmentioning
confidence: 99%
“…When the chondrolabral junction is too damaged to be preserved, labral reconstruction is recommended given its promising short- to midterm clinical outcomes. 11,15,19,20,31 Nonetheless, the reported conversion rate of labral reconstruction to total hip arthroplasty (THA) is relatively high, 7,15,20,28,32 which remains a great challenge for the treatment of irreparable labral tears. Moreover, our previous study in a porcine model showed that the slow and insufficient vascular ingrowth within the articular half could cause poor healing of the reconstructed autograft labrum.…”
mentioning
confidence: 99%
“…The series from Chicago (Illinois, USA) is a propensity-matched study comparing athletes undergoing revision labral repair with non-athletes. 5 Outcomes are to a very satisfactory two years, and the authors assessed them with patient-reported outcome measures (PROMs) and based on return to sports. The PROMs reported by the authors are the modified Harris Hip Score (mHHS), the Nonarthritic Hip Score (NAHS), the Hip Outcome Score-Sport Specific Subscale (HOS-SSS), and the visual analogue scale (VAS) for pain.…”
Section: Labral Reconstruction For Revision Labral Tear – Worth Doing...mentioning
confidence: 99%
“…Therefore, several authors now believe that labral reconstruction should be the treatment of first choice for labral degeneration or defect. 3 , 4 , 5 …”
mentioning
confidence: 99%